Back Cover: Two‐Dimensional NMR Spectroscopy with Temperature‐Sweep (ChemPhysChem 11/2014). Issue 11 (4th August 2014) - Bermel, Wolfgang; Dass, Rupashree; Neidig, Klaus‐Peter; Kazimierczuk, Krzysztof
<x xml:space="preserve">Abstract</x> The picture shows a spectral snapshot from a time‐resolved two‐dimensional NMR experiment with temperature sweep. The temperature is swept linearly in parallel to signal sampling. The new experiment proposed on p. 2217 by K. Kazimierczuk et al. allows precise, on‐the‐fly observation of various phase transitions. Dedicated processing with a compressed sensing algorithm provides a movie‐like 2D spectrum that changes continuously with temperature.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>